Game-based Learning in Improving Junior High School Students’ Classroom Participation - Wildatuzzahrany Wildatuzzahrany; Ade Hidayat (Media Akademika Publisher, 2025)
English has been a subject taught in various schools in Indonesia for several years. However, in the learning process, many students still face challenges, particularly in classroom participation. This difficulty is further exacerbated if teachers still apply traditional methods such as lectures that lack active student participation. Therefore, it is important to use appropriate learning methods to create an effective and enjoyable learning atmosphere. One innovative approach that can be used is Game-Based Learning, a method that combines game elements into teaching and learning activities to create a more interactive and engaging learning experience. This approach is believed to improve student understanding, including vocabulary enrichment. This study aims to determine the effectiveness of the Game-Based Learning method in improving classroom participation of eighth-grade students at MTs Nurul Qur'an. The study was conducted using the Classroom Action Research (CAR) method, consisting of two cycles, and involving 25 students as research subjects. Data collection was conducted through observations administered during the Game-Based Learning implementation. The results showed a significant increase in students' participation after the implementation of Game-Based Learning. Therefore, it can be concluded that this method is effective in improving English vocabulary mastery while encouraging active student engagement in class.